Analysing the Effect of Cassava Flour as a Mixture on the Physical, Mechanical, and Durability Properties of High-Strength Concrete - Marwa Gumma Omer Adam; David O. Koteng; Joseph Ng’ang’a Thuo; Mohammed Matallah (Salehan Institute of Higher Education, 2022)
The availability, cost, and environmental impact of chemical admixtures are reduced when natural substitute materials are incorporated into the concrete as an admixture. This paper outlines the findings of a study that looked at the physical characteristics of fresh and hardened concrete made with Portland pozzolanic cement CEM II/B-P blended with cassava flour up to 5% by weight of cement. A low water/binder ratio of 0.35 was used together with a carboxylate-based superplasticizing admixture to produce high strength. In fresh-state concrete, the initial and final setting times, soundness, and consistency were found to increase with increased cassava flour content, whereas the compacting factor and slump were observed to decrease. In the hardened state, compressive strengths were determined at 3, 7, 14, 28, 56, and 90 days, while split tensile and flexural strengths were investigated at 28 days. Similarly, dry density and porosity were also investigated at 28 days. Water absorption was also studied as a potential indicator of durability in hardened concrete. Scanning electron microscopy characterization of cassava flour revealed porous particles of irregular shape. On the other hand, X-ray diffraction imaging showed that the primary chemicals in cassava flour are silicon dioxide (50%), calcium oxide (17%), and aluminium oxide (7%). All of the mixes that incorporated cassava flour were stronger than the control mix, with the 3% cassava flour combination producing the best results. Doi: 10.28991/CEJ-2022-08-12-015 Full Text: PDF